CHALLENGES AND OPPORTUNITIES OF DIGITAL AUDITING: A LOOK BEYOND THE YEAR 2020 - Ilmawan, Faiz Nuha; Bawono, Icuk Rangga (Jurnal Magister Akuntansi Trisakti, 2024)
Digital technologies, including artificial intelligence (AI), big data, and blockchain, have significantly changed the auditing landscape. This study aims to explore the impact of these technologies on audit practices in the future, focussing on the challenges and opportunities auditors face. Using a qualitative approach, the study involved in-depth interviews, case studies, and participatory observations of several companies adopting digital technology in their audits. The study results show that applying digital technology can increase efficiency, accuracy, and transparency in the audit process. AI and big data enable faster and more comprehensive data analysis, while blockchain improves the reliability and integrity of audited data. However, the study also reveals significant challenges, such as a lack of technology skills among auditors, concerns related to data security and privacy, and potential changes in the role of auditors that could affect audit quality. On the other hand, the digital era also opens opportunities for auditors to engage in multidisciplinary collaboration and develop new competencies relevant to modern technology. However, to make the most of these opportunities, auditors need to maintain strong ethical principles and comply with applicable regulations.